Palmitic acid of Musa Paradisiaca induces apoptosis through caspase-3 in human oral squamous cell carcinoma - Budi, H. S.; S., Anitasari; Ulfa, N. M.; Setiabudi, M. A.; Ramasamy, R.; Wu, C. Z.; Shen, Y. K. (Verduse Editore, 2022)
Objective: Despite apoptosis processes being conserved, cancer cells have developed mechanisms to inhibit apoptosis by altering anti-apoptotic molecules or inactivating pro-apoptotic. The aim of this study was to determine the palmitic acid of Musa paradisiaca var. sapientum (L) Kunz (MP) stem extracts against human oral squamous cell carcinoma (hOSCC) through caspase-3. Materials and Methods: Ethanol and ethyl acetate extracts of MP stem were analyzed by gas chromatography-mass spectrometry (GC-MS). Computerized models of chemically active compounds were used to predict anticancer activity. Cytotoxicity was evaluated in Artemia salina Leach and hOSCC (OM-1) culture at concentrations 100, 90, 80, 70, 60, 50, 40, 30, 20, and 10 µg/mL respectively. The expression level of caspase-3 on hOSCC was measured by enzyme-linked immunoassay (ELISA). Results: We found seven chemically active compounds in the ethanol extract and 15 compounds in the ethyl acetate extract of MP stem. The major component was hexadecanoic acid of palmitic acid derivates, and this was predicted to have anticancer activities as apoptosis through caspase-3 stimulants. However, cytotoxicity effects against hOSCC culture were assessed by values of the 50% inhibitory concentration (IC50) of 15.00 µg/mL for the ethanol extract, and an IC50 of 10.61 µg/mL for the ethyl acetate. There was a significant increase of caspase-3 level on treatment groups compared to control. Conclusions: Hexadecanoic acid of MP stem extracts has anticancer activity by inhibiting cell growth of hOSCC culture through caspase-3 stimulants.